NHS Scotland DNACPR and CYPADM integrated policies – development of quality measures. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Spiller, Juliet; Kiehlmann, Peter; Davison, Hilary; Murphy, Dermot; Wilkie, Rosalie
Abstract : Background: In May 2010 National Health Service (NHS) Scotland published Europe's first fully integrated national policy for Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) decision making and communication in adults. The Scottish Government led the development of this policy, based on previous work from NHS Lothian, in response to a specific recommendation by the Public Audit Committee following the Audit Scotland publication 'Review of Palliative Care Services in Scotland. Living and Dying Well' the national action plan for palliative care in Scotland also requested an integrated approach to DNACPR. All Scottish Health Boards committed to implementation of the policy by October 2010. Shortly after this the Children/Young People Acute Deterioration Management (CYPADM) Policy was also published and implemented across Scotland. Aims: These integrated DNACPR policies aim to prevent inappropriate, futile and/or unwanted attempts at CPR. They are intended as a positive step to help a person's wishes to be followed at the end of life irrespective of whether they are being cared for in hospital, hospice, care home or in their own homes. This specific work aimed to develop measures to assess the impact of these policies on patient care across Scotland. Method: Health Improvement Scotland undertook the ongoing review and evaluation of the DNACPR and CYPDM policies in consultation with a core multidisciplinary group including representatives from all Health Boards, the Scottish Ambulance Service, the Care Commission and NHS 24. Measures have been developed and agreed which will establish the extent to which these policies are impacting on patient care with regard to inappropriate CPR attempts, expected death and anticipatory care planning. Conclusions: Policies which facilitate an integrated approach to DNACPR decision-making and communication in adults and children have been implemented across Scotland. Quality measures have been developed to assist Health Boards in establishing the impact of these policies on patient care.